FEASIBILITY AND EFFECTS OF CHAIR YOGA TO MANAGE DEMENTIA SYMPTOMS IN OLDER ADULTS. (11th November 2018) - Park, J; Tolea, M; Rosenfeld, A; Arcay, V; Karson, J; Lopes, Y; Small, K; Galvin, J
Abstract: This study tested feasibility of community-dwelling older adults with dementia (mild, moderate, or moderate to severe) safely completing a chair yoga (CY) intervention. We examined effects of CY on physical function, behavioral and psychological symptoms, quality of life, and sleep quality (daytime sleepiness, nighttime sleep). Participants attended twice-weekly 45-minute CY sessions for 12 weeks (24 sessions). Instruments included a demographic and health information questionnaire, standardized assessment of physical function, psychological symptoms (depression and anxiety) and behavior symptoms (agitation), quality of life (QoL), and sleep quality. One-way repeated measures of analysis of variance (ANOVA) compared baseline, midline (6 weeks), and post-intervention (12 weeks) scores on the measures of interest. Ten participants started the intervention, 8 completed it and provided data at all three data collection points; no adverse events were associated with CY. Most participants were diagnosed with Alzheimer's disease. QoL scores increased from baseline to midline to post-intervention (34.0 ± 2.3, 35.1 ± 3.5, 35.6 ± 3.8, respectively); depression and anxiety scores improved from baseline to midline (7 ± 2.4 to 6.6 ± 3.2 and 7.25 ± 3.8 to 6.5 ± 4.2, respectively). Physical function scores did not change from baseline to midline and decreased from midline to post-intervention (8.3 ± 3.7 to 7.4 ± 3.3). The 12-week CY intervention was safe for older adults with moderate to severe levels of dementia. Although the study demonstrated feasibility of retaining participants, the small sample size limited the power to evaluate the magnitude of effects of the intervention on dementia symptoms.